Implementing large- scale data quality validation in a national arthroplasty registry to improve compliance. (September 2022) - Boulton, C.; Harrison, C.; Wilton, T.; Armstrong, R.; Young, E.; Pegg, D.; Wilkinson, J. M.
No abstract available